THE ROLE OF OLFACTORY FUNCTION AND MULTIMORBIDITY IN COGNITIVE IMPAIRMENT: Peranan Fungsi Penghidu dan Multimorbiditas Terhadap Fungsi Kognitif - Kristian, Kevin; Vebriana, Gennesia; Hardi, Nicholas; Turana, Yuda; Handajani, Yvonne Suzy (Jurnal Berkala Epidemiologi, 2025)
Background: As the population ages, the issue of cognitive impairment is becoming increasingly worrisome, especially with the rise in conditions like multiple chronic diseases and loss of smell among the elderly. Purpose: The goal of this research is to explore how multiple chronic diseases, sense of smell, and cognitive impairment are linked among the senior population. Methods: This study involved 128 individuals at a senior community in Jakarta with an average age of 68.34 years. The presence of multiple chronic diseases was determined by looking for highest prevalence of disease pairs, and the sense of smell was tested with an 8-smell test. Cognitive function was measured with the CERAD questionnaire, with a score below 52 indicating cognitive impairment. The analysis included Chi-square tests at a 95% confidence level. Results: The findings suggest a clear link between lower levels of education and cognitive impairment (p=0.018; OR=3.214), as well as between loss of smell and cognitive deterioration (p=0.049; OR=2.565). However, having more than three chronic diseases was found to significantly increase the risk of cognitive impairment (p=0.018; OR=2.678), but there was no significance to support that certain disease pairs were more likely to lead to cognitive impairment. Conclusion: This research underscores the significance of sense of smell and the presence of multiple chronic diseases, especially in greater numbers, as major risk factors for cognitive impairment in the elderly.